2016
DOI: 10.1016/j.ssmph.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Jedi public health: Co-creating an identity-safe culture to promote health equity

Abstract: The extent to which socially-assigned and culturally mediated social identity affects health depends on contingencies of social identity that vary across and within populations in day-to-day life. These contingencies are structurally rooted and health damaging inasmuch as they activate physiological stress responses. They also have adverse effects on cognition and emotion, undermining self-confidence and diminishing academic performance. This impact reduces opportunities for social mobility, while ensuring tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 77 publications
4
69
0
2
Order By: Relevance
“…Geronimus et al. () introduced the “Jedi Public Health (JPH)” as one solution to the effects of racism. This framework, “…focuses on changing features of settings in everyday life, rather than individuals, to promote population health equity, a high priority, yet, elusive national public health objective” (p. 105).…”
Section: Policy Responses Should Be Multilevelmentioning
confidence: 99%
See 3 more Smart Citations
“…Geronimus et al. () introduced the “Jedi Public Health (JPH)” as one solution to the effects of racism. This framework, “…focuses on changing features of settings in everyday life, rather than individuals, to promote population health equity, a high priority, yet, elusive national public health objective” (p. 105).…”
Section: Policy Responses Should Be Multilevelmentioning
confidence: 99%
“…Geronimus et al. () have argued that there is a need for expansion as well as a reorientation of efforts to eliminate population health inequities. In the JPH framework, policies and interventions should remove all the discrediting cues in daily life of Blacks and other minority groups.…”
Section: Policy Responses Should Be Multilevelmentioning
confidence: 99%
See 2 more Smart Citations
“…A substantial literature has examined income and other SES gradients in health within Latino samples and has typically found smaller health-SES gradients than are found in other racial/ethnic groups (Ranjit et al, 2007; Sánchez-Vaznaugh et al, 2009), and sometimes found nonexistent (Angel et al, 2001) or reversed (Collins et al, 2001; Geronimus et al, 2015) gradients. It has been theorized that the potential health advantages of increasing income are not as beneficial to Latinos (or at least some Latino subgroups) because increasing income comes at the cost of high-effort striving and coping that is in itself detrimental to health (Geronimus et al, 2016; Pearson, 2008) or comes with exposure to a range of other social and racialized stressors that counteract potential health benefits (Gallo et al, 2013). …”
Section: Discussionmentioning
confidence: 99%